Microbiological characteristics and risk factors on prognosis associated with Acinetobacter baumannii bacteremia in general hospital: A single-center retrospective study - Wei, Zhiyong; Zhou, Shuai; Zhang, Ying; Zheng, Lin; Zhao, Lina; Cui, Yan; Xie, Keliang (Frontiers in Microbiology, 2022)
Objective：Acinetobacter baumannii is one of the most important pathogenic bacteria causing nosocomial infections and has a high mortality rate. Assessment of the microbiological characteristics and risk factors on prognosis associated with A.baumannii is essential. In this study, we aimed to investigate the clinical characteristics and prognostic risk factors of patients with A.baumannii bacteremia. Patients and Methods：This study retrospectively analyzed the antibiotic resistance of pathogens based on the clinical data of A.baumannii bacteremia patients presented in a tertiary teaching hospital from 2017 to 2022. Logistic regression and decision tree identified the prognostic risk factors for patients with baumannemia. Kaplan-Meier method was used for survival analysis between MDR and Non-MDR groups. The area under receiver-operating characteristic curve (ROC curve) was used to compare the predictive value of the APACHE II score and SOFA score. Results：A total of 110 patients with positive A. Baumannii blood cultures were included. Most of the patients were from ICU wards. The drug sensitivity results showed that the resistance rate of A. baumannii to colistin was the lowest (1.1%), followed by tigecycline (3.6%). The survival time of MDR group was significantly shorter than that of Non-MDR group. Multivariate analysis showed that, APACHE II score and SOFA score were independent risk factors affecting the prognosis of 28 days of A.baumannii bacteremia. And both scores displayed excellent AUROCs (SOFA:0.909, APACHE II: 0.895 in predicting 28-day mortality). The two scoring systems were highly correlated and predicted no significant difference (r2=0.4410, P＜0.001). We found that SOFA >7 and APACHE II >21 are associated with significantly higher mortality rates. Conclusion：A.baumannii bacteremia have the highest incidence in the ICU, with high drug resistance and mortality rates. The survival time of patients with MDR A. Baumannii bacteremia was significantly shortened. The SOFA score and APACHE II score can reflect the severity of A.baumannii bacteremia patients and evaluate the 28-day prognosis. In addition, for the convenience of calculation, the SOFA score may be more clinically useful than the APACHE II score in predicting the mortality rate of A.baumannii bacteremia.